2004
DOI: 10.1152/ajpcell.00131.2003
|View full text |Cite
|
Sign up to set email alerts
|

Actin reorganization and morphological changes in human neutrophils stimulated by TNF, GM-CSF, and G-CSF: the role of MAP kinases

Abstract: Stimulation of human neutrophils with tumor necrosis factor-α (TNF), granulocyte-macrophage colony-stimulating factor (GM-CSF), or granulocyte CSF (G-CSF) resulted in decreased fluorescence intensity of FITC-phalloidin (actin depolymerization) and morphological changes. Cytokine-induced actin depolymerization was dependent on the concentration of cytokines used as stimuli. The maximal changes were detected at 10 min after stimulation with TNF or GM-CSF and at 20 min after stimulation with G-CSF. Cytokine-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
70
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 50 publications
15
70
1
1
Order By: Relevance
“…Our present results provide further evidence for the concept of immune selection in neoplastic development by showing that CTL selection pressure can lead to a striking adaptation of the tumor target, involving morphological change to escape immune surveillance. Although the mechanisms by which CTL selection pressure contributes to morphological changes remain to be fully elucidated, it has been recently reported that cytokines, including TNF, can induce actin depolymerization and morphological changes through activation of ERK and orp38 mitogen-activated protein kinase (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our present results provide further evidence for the concept of immune selection in neoplastic development by showing that CTL selection pressure can lead to a striking adaptation of the tumor target, involving morphological change to escape immune surveillance. Although the mechanisms by which CTL selection pressure contributes to morphological changes remain to be fully elucidated, it has been recently reported that cytokines, including TNF, can induce actin depolymerization and morphological changes through activation of ERK and orp38 mitogen-activated protein kinase (28).…”
Section: Discussionmentioning
confidence: 99%
“…7 Since meiotic spindles in oocytes lack centrosomes, MTOCs (microtubule organization centers) act as centrosomes, indicating that a specialized mechanism may be responsible for the off-centre positioning of the spindles. Cdc42, aPKC, Formin, Fyn, Myosin, MLCK and the MAPK pathway are involved in spindle positioning in mouse oocytes.…”
Section: Wave2 Regulates Meiotic Spindle Stability Peripheral Positimentioning
confidence: 99%
“…In fact, activation of overlapping but distinct MAPK subtype cascades has been demonstrated in human neutrophils stimulated with different agonists (15)(16)(17)(18)(19). Therefore, to delineate the signaling intermediates activated by bacterial DNA, neutrophils were stimulated with E. coli DNA (100 g/ml) for different times at 37°C.…”
Section: Neutrophil Mapks Are Activated By Bacterial Dnamentioning
confidence: 99%